Biophysical and flavonoid-binding studies of the G protein ectodomain of group A human respiratory syncytial virus - Machado, Vitor Brassolatti [UNESP]; Maróstica de Sá, Jéssica [UNESP]; Miranda Prado, Ana Karla [UNESP]; Alves de Toledo, Karina [UNESP]; Regasini, Luis Octávio [UNESP]; Pereira de Souza, Fátima [UNESP]; Caruso, Ícaro Putinhon [UNESP]; Fossey, Marcelo Andres [UNESP] (Elsevier, 2019)
The human Respiratory Syncytial Virus (hRSV) is the major causative agent of lower respiratory tract diseases in infants, young children and elderly. The membrane protein G is embedded in the viral lipid envelope and plays an adhesion function of the virus to host cells. The present study reports the production of the group A hRSV recombinant G protein ectodomain (edG) and its characterization of secondary structure and thermal unfolding by circular dichroism (CD), as well as the binding investigation of flavonoids quercetin and morin to this protein by fluorescent quenching. CD data reveal that edG is composed mostly of β-structure and its melting temperature is of 325 K. Fluorescence quenching experiments of hRSV edG show that the dissociation constants for the flavonoids binding are micromolar and the binding affinity for the edG/quercetin complex is inversely dependent on rising temperature while is directly dependent for the edG/morin interaction. The thermodynamic parameters suggest that hydrophobic contacts are important for the edG/morin association while van der Waals forces and hydrogen bonds contribute to the stabilization of the edG/quercetin complex. Thus, data reported herein may contribute to the development of new treatment strategies that prevent the viral infection by hRSV.
Keywords: Biochemistry; Biophysics; Molecular biology